2014
DOI: 10.12820/rbafs.v.19n6p732
|View full text |Cite
|
Sign up to set email alerts
|

Respostas hemodinâmicas durante e após sessão de pilates em comparação com exercício aeróbico e resistido

Abstract: ResumoOs objetivos foram verificar a segurança da sessão Pilates (SP) por meio do duplo produto e comparar a hipotensão (HPE) com uma sessão aeróbia (SA) e treinamento resistido (SR) em adultos jovens analisando as alterações e comportamento hemodinâmico advindo durante as sessões. 12 adultos jovens do sexo masculino (23,3 ± 2 anos; 23,9 ± 1 kg/m²) realizaram três sessões exercícios: SA, SR e SP e uma sessão controle (SC) (60 minutos cada). A pressão arterial (PA) e a frequência cardíaca (FC) foram registradas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…However, when analyzing a single session of Pilates, hypotensive responses do not look promising in healthy populations. In studies similar to the present study, with normotensive women after menopause [19], young men [13] or women already trained in the modality, mostly normotensive [20], demonstrated that there was no hypotensive effect of a single Pilates session when comparing to the control in the first 60 minutes post exercise. This result is maintained even though it has increased the bioavailability of salivary nitrite (nitric oxide precursor, a potent vasodilator) [19].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…However, when analyzing a single session of Pilates, hypotensive responses do not look promising in healthy populations. In studies similar to the present study, with normotensive women after menopause [19], young men [13] or women already trained in the modality, mostly normotensive [20], demonstrated that there was no hypotensive effect of a single Pilates session when comparing to the control in the first 60 minutes post exercise. This result is maintained even though it has increased the bioavailability of salivary nitrite (nitric oxide precursor, a potent vasodilator) [19].…”
Section: Discussionsupporting
confidence: 69%
“…The sample size (n = 15) was calculated using G*Power 3.1 (α = 0.05; power = 0.80; effect size = 0.7). This effect size was calculated from the average difference in systolic hypotension between the Pilates and control sessions, considered as 3.3±3.6 mmHg [13]. Since we did not find studies with Pilates and 24-hour measurements, the effect size found (ES = 0.91) was reduced to 0.7 to suit a more pessimistic situation with 24-hour measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation